SMART ATTENDENCE MONITERING SYSTEM - NARAYANA, Dr.V.A; REDDY, G.KARTHIK; RAVIKIRAN, K.; MANISH; NIKHIL (The journal of contemporary issues in business and government, 2021)
Attendance management has been a great challenge over the years . Ranging from university to polytechnics, colleges of educations and secondary schools, quality attendance management has been a freak. Manual authentication of attendance of logbooks has become an arduous task and this is also time-consuming. The academic attendance policy has generated a lot of questions at various quarters. All academic institutions have certain criteria for students regarding their attendance in class and examinations. The importance of student attendance in class cannot be over emphasized, as a result of this, administrators and lecturers of various academic institutions are concerned with the attendance irregularities. In the process of admitting students into an examination hall, 70% of attendance must be met and also considered for grade computation, therefore there is a huge need for monitoring and recording students’ attendance. This brings about the need to have a tool to control students’ attendance. The existing model of manual attendance monitoring (using paper sheets and an old file system) is not efficient and it is also time consuming. These aforementioned shortcomings among others serve as justification for migrating from manual based to the proposed system. The system is based on barcode reader technology and the details of this system are presented in this paper. The system can be easily accessed by the lecturers and most importantly, the reports can be generated in real-time processing, thus, providing valuable information about the students.